In vitro B cell experiments explore the role of CD24, CD38, and energy metabolism in ME/CFS - Armstrong, Christopher W.; Mensah, Fane F. K.; Leandro, Maria J.; Reddy, Venkat; Gooley, Paul R.; Berkovitz, Saul; Cambridge, Geraldine (Frontiers in Immunology, 2024)
Disturbances of energy metabolism contribute to clinical manifestations of Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS). Previously we found that B cells from ME/CFS patients have increased expression of CD24, a modulator of many cellular functions including those of cell stress. The relative ability of B cells from ME/CFS patients and healthy controls (HC) to respond to rapid changes in energy demand were compared. CD24, the ectonucleotidases CD39, CD73, the NAD-degrading enzyme CD38 and mitochondrial mass (MM) were measured following cross-linking of the B cell receptor (BCR) and co-stimulation with either T cell dependent or Toll-like receptor-9 dependent agonists. Levels of metabolites consumed/produced were measured using 1H-NMR spectroscopy and analysed in relation to cell growth and immunophenotype. Proliferating B cells from patients with ME/CFS showed lower mitochondrial mass and a significantly increased usage of essential amino acids compared those from HC, with a significantly delayed loss of CD24 and increased expression of CD38 following stimulation. Immunophenotype results suggested the triggering of a stress response in ME/CFS B cells associated with increased usage of additional substrates to maintain necessary ATP levels. Disturbances in energy metabolism in ME/CFS B cells were thus confirmed in a dynamic in vitro model, providing the basis for further mechanistic investigations.